Gait recognition a challenging signal processing technology for biometric identification. - Boulgouris, N.V (IEEE Signal processing magazine)
This article provides an overview of the basic research directions in the field of gait analysis and recognition. The recent developments in gait research indicate that gait technologies still need to mature and that limited practical applications should be expected in the immediate future. At present, there is a potential for initial deployment of gait for recognition in conjunction with other biometrics. However, future advances in gait analysis and recognition - an open, challenging research area - are expected to result in wide deployment of gait technologies not only in surveillance, but in many other applications as well. This article exposes the gait analysis and recognition problem to the signal processing community and it will stimulates the involvement of more researchers in gait research in the future.